Bourdieu, the boom and cashed-up Bogans. (June 2013) - Pini, Barbara; Previte, Josephine
For a number of years the social and cultural landscape of Australia has been haunted by the figure of 'the Bogan', which, although malleable, has typically been deployed as a negative descriptor of the white working-class poor. The nation's most recent resource boom has, however, seen the emergence of a new classed figure that of the 'CUB' (cashed-up Bogan). In examining the figure of the CUB, this article draws on Bourdieu's notions of capital, distinction and taste in light of Skeggs' claim that Bourdieu may not be as useful in the Australian context. Her point of departure is that class involves more a 'display of money rather than the display of culture'. We demonstrate the importance of cultural capital in defining and disparaging the CUB and in asserting the legitimacy of elite cultural dispositions, while pointing to the emergence of spiritual capital and environmental capital as part of this process.